DISTAL SPLENORENAL VENOUS ANASTOMOSIS IN TREATMENT OF DIABETES MELLITUS - T. I. Shraer; N. S. Rozina; A. A. Salmayer (Вестник трансплантологии и искусственных органов, 2010)
We studied the outcomes of the operations for distal splenorenal venous anastomosis of 134 patients with type 1 diabetes mellitus. We have noticed the significant improvement of patient’s general condition due to spasmolytic effect of glucagon, bypassed to blood circulation without coming through liver and also a stabilization of glyce- mia because of a restoration of insulin-glucagon ratio in systemic circulation. The effect of a surgery depends on a stage of microangiopathy and nephrosclerosis.